Innovation implementations in Malaysian firms: Process, problems, critical success factors and working climate - Mohamed, M.Zain (Elsevier Science, 1995)
This paper reports on the results of a field study on the implementation of innovations by eight firms manufacturing in Malaysia. The study investigated the innovation process followed by the firms, the problems faced by them, the factors perceived to be favourable to the success of innovation implementation, and the working climates of the firms. The results from the study indicate that the innovation process followed by the firms and the factors favourable to innovation implementation were similar to those found in the literature (mainly Western). However, not all of the factors cited are applicable to all the firms and industry sectors, which indicates the contingent nature of the innovation. There were also differences in the types of problem faced by the firms when implementing their innovations. Generally, the more innovation-active firms (those which introduced and implemented more incremental innovations, continuous improvements and technological innovations, those which interacted more with their environments, and those which organized more training programmes or campaigns aimed at encouraging the employees to be creative and innovative) were found to have encountered less behavioural problems when implementing their innovations. The more innovation-active firms were therefore more successful in their implementation efforts than the less innovation-active ones. Finally, the results also show that in order for firms to be successful at implementing innovations they need to provide a favourable working climate for their workers.